2020
DOI: 10.1021/acs.est.9b07042
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Tris(2-chloroethyl) Phosphate (TCEP) in Sediment Microcosms and the Adaptation of Microbial Communities to TCEP

Abstract: Tris­(2-chloroethyl) phosphate (TCEP), a typical chlorinated organophosphate ester (OPE), is an emerging contaminant of global concern because of its frequent occurrence, potential toxic effects, and persistence in the environment. In this study, we investigated the microbial TCEP biotransformation and the development of microbial communities in sediment microcosms with repeated TCEP amendments. The TCEP degradation fitted pseudo-zero-order kinetics, with reaction rates of 0.068 mg/(L h) after the first spike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…These results revealed that ACP played a key role in the hydrolysis of OPEs in plant hydroponic systems. It was reported that the AKP and ACP genes were significantly upregulated as a response to tris­(2-chloroethyl) phosphate (TCEP) exposure in the microbial communities of sediments, implying that these two enzymes might participate in the hydrolysis of TCEP . Under P-deficient conditions, prokaryotes, such as algae and microorganisms, could hydrolyze OPEs into inorganic P and used OPEs as the sole P source. , Therefore, with the extension of exposure time, we speculated that the plant could utilize OPEs as the source of P by hydrolyzing them into inorganic P under the pressure of P deficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results revealed that ACP played a key role in the hydrolysis of OPEs in plant hydroponic systems. It was reported that the AKP and ACP genes were significantly upregulated as a response to tris­(2-chloroethyl) phosphate (TCEP) exposure in the microbial communities of sediments, implying that these two enzymes might participate in the hydrolysis of TCEP . Under P-deficient conditions, prokaryotes, such as algae and microorganisms, could hydrolyze OPEs into inorganic P and used OPEs as the sole P source. , Therefore, with the extension of exposure time, we speculated that the plant could utilize OPEs as the source of P by hydrolyzing them into inorganic P under the pressure of P deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Accumulation of OPEs in humans would cause a threat to human health. 14 Several studies have found that OPEs are likely to transform into other compounds in organisms, such as microorganisms, 15 fish, 16 and humans. 17 Phosphodiesters, the hydrolysis products of OPEs, have been frequently detected in fish 18 and humans, 19 and this evidence indicated that phosphodiester might be the main transformation product of OPEs in organisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The environmental occurrence of di-OPEs is likely related to the fate of tri-OPEs, and therefore, the mechanism of migration and transformation of tri-OPEs to di-OPEs in different environmental matrices, especially under environmental conditions, needs to be fully addressed. Hydrolytic, thermal, photo, and microbial degradation of selected tri-OPE compounds have been investigated, mostly in spiked samples under laboratory controlled conditions. , A recent study comprehensively investigated the microbial biotransformation of TCEP and found that microbial TCEP degradation fitted well with pseudo-zero-order kinetics . In addition to BCEP, several other degradation products were identified, including monochloroethyl phosphate, bis (2-chloroethyl) 2-hydroxyethyl phosphate, phosphoric bis (2-chloroethyl) (2-oxoethyl) ester, phosphoric acid bis (2-chloroethyl)­(carboxymethyl) ester, and 2-chloroethyl 2-hydroxyethyl hydrogen phosphate .…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolytic, thermal, photo, and microbial degradation of selected tri-OPE compounds have been investigated, mostly in spiked samples under laboratory controlled conditions. , A recent study comprehensively investigated the microbial biotransformation of TCEP and found that microbial TCEP degradation fitted well with pseudo-zero-order kinetics . In addition to BCEP, several other degradation products were identified, including monochloroethyl phosphate, bis (2-chloroethyl) 2-hydroxyethyl phosphate, phosphoric bis (2-chloroethyl) (2-oxoethyl) ester, phosphoric acid bis (2-chloroethyl)­(carboxymethyl) ester, and 2-chloroethyl 2-hydroxyethyl hydrogen phosphate . It is desirable to illuminate the degradation kinetics and pathways of tri-OPEs with different functional groups under environmental or environment-relevant conditions and to identify degradation products besides di-OPEs.…”
Section: Resultsmentioning
confidence: 99%
“…For the four BTPs, the errors between theoretical and measured mass were within 3.1 ppm, which is lower than mass accuracy tolerance of 5 ppm. 74 The other three BTPs (ciprofloxacin, N-acetyl-sulfadiazine, and Nacetyl-sulfamethoxazole) were identified with reference standards using the UPLC−MS/MS based on retention time, precursor, and product ions (Table S13). This is the first study to report BTPs of antibiotics in sea cucumber tissues, which is of importance to understand the toxicological effects and conduct risk assessment associated with sea cucumbers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%